Outcomes of Pharmaceutical Care Development in a Tuberculosis Outpatient Clinic at Vajira Hospital - Phochanasomboon, Krittima (Journal of Health Sciences and Wellness, 2025)
Pharmaceutical care for tuberculosis (TB) patients aims to enhance clinical decision support systems and reduce medication prescribing errors. This retrospective descriptive study was conducted to examine medication errors, adverse drug reactions (ADRs), and patient waiting times for receiving medications. The study population included TB patients who received care between January 2 and September 27, 2022 (Phase 1: traditional pharmaceutical care), and between January 2 and December 28, 2023 (Phase 2: enhanced pharmaceutical care). Data were collected using a TB pharmaceutical care documentation form adapted from the Thai national TB control guidelines. The collected data included patient demographics, clinical information, prescription data, and waiting times for medication dispensing. In Phase 1, 309 TB patients were included. The analysis identified two predominant types of prescribing errors: inadequate drug quantity (67.43%) and improper dosage prescriptions (18.81%). ADRs were reported as minor in 12.94% of patients and major in 14.89%. In Phase 2, 342 TB patients were included. During this phase, inadequate drug quantity errors were reported at the level of 50.55%, while improper dosage prescriptions were at 4.40%. ADRs were reported in 20.76% of patients, including both minor and major reactions. The study concludes that enhanced pharmaceutical care tends to reduce prescribing errors and also improves the detection of ADRs. The clinical decision support system is adaptable to hospital settings; however, further improvements are recommended, particularly in the calculation of pill quantities, the development of medication order sets for patients with complications, and the application of inferential statistical methods in future studies.